EMBRACING THE CIRCULAR ECONOMY: A PARADIGM SHIFT FOR SUSTAINABLE PROSPERITY - Ionut Marius CROITORU; Mircea Adrian GRIGORAS; Agatha POPESCU; Brîndușa Antonia GRIGORAŞ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study aimed to set up a review of the scientific literature concerning the circular economy, called to become a viable alternative to the linear "take-make-dispose" approach and assure sustainability. It synthesizes, in a logical order, the main aspects regarding the circular economy versus linear economy and has a critical approach comparatively pointing out the benefits and restrains. The two economic models are illustrated in schemas in such a way to clearly distinguish the difference in their objectives, principles and benefits. Also, the study presents the key policies and initiatives of the circular economy, highlighting the EU's commitment and the metrics for measuring the circularity. Regarding the circular agriculture, it is emphasized the efficiency in resource use, recycling, and waste reduction, closed nutrient loops, biodiversity conservation, climate change mitigation, food production and consumption, and the creation of economic value. Circular agriculture practices such as agroforestry, crop rotation, composting organic farming, and regenerative agriculture are also presented. Circularity in agriculture should cease to be seen merely as a concept, it should be considered a necessity for building a sustainable and resilient economy of the future.